Interactive Effect of Salinity and Temperature on Artemia Cyst Hatching Percentage - Magda S Elwalid; Randa T Elbeshti; Siddiq M EL-Ajnaf (Libyan Journal of Medical and Applied Sciences, 2025)
This study aims to enhance aquaculture efficiency by evaluating the interactive effects of salinity and temperature on hatching success in two Artemia species: Artemia salina, collected from the Libyan Zwara salt flats, and Artemia franciscana, imported from the United States. Experimental trials were conducted using 1.6 g of dry cysts per species, exposed to seven salinity levels (20–40 g/L) and three temperature conditions (25°C, 28°C, and 32°C).Results indicated that A. salina achieved a maximum hatching rate of 62.5% at 28°C and 25 g/L after 48 hours, while A. franciscana reached a peak of 96.8% at 25°C and 25 g/L after 36 hours. These findings underscore distinct interspecific differences in hatching efficiency and environmental tolerance. A. franciscana exhibited greater resilience to elevated salinity and temperature levels, maintaining high hatching success even at 32°C. In contrast, A. salina showed a marked decline in hatching rates under the same thermal condition.Two-way Anova analysis revealed statistically significant interactions between salinity and temperature, emphasizing the importance of optimizing these parameters to improve cyst hatchability in hatchery settings.